Impact of incarceration experiences on reported HIV status and associated risk behaviours and disease comorbidities. - Heimer, Robert; Levina, Olga S; Osipenko, Victoria; Ruiz, Monica S; Sergeyev, Boris; Sirotkin, Aleksander V; Vyshemirskaya, Inna (European journal of public health, 2015)
The Russian human immunodeficiency virus (HIV) epidemic among people who inject drugs (PWID) originated in Kaliningrad, but research into risk behaviours among PWID has been lacking. The potential for heterosexual spread has not been analysed.